The affections of group facebook user-generated content on tourists’ purchase intention – the study in Da Lat, Vietnam - Nguyễn, Thanh Tùng (2023)
Consulting users on social networks when preparing to travel has become a habit of tourists. However, the scientific literature on this is relatively limited. This research was conducted to test the model of predictors of group Facebook user-generated content affecting tourists’ purchase intention. To do this, online surveys were constructed, and data were collected from tourists and people planning to travel to Dalat. Findings illustrated that there are considerable and meaningful relationships between factors of Facebook user-generated content and tourists’ purchase intention. The study, moreover, concludes with suggestions for hospitality management, admin team, and Facebook businessman etc. to better off from user-generated content in online attracting tourists